Faktor yang Mempengaruhi Business Sustainability Pada Rumah Sakit di Pekanbaru - Lora Natalia Hutagaol; Zul Azmi; Mentari Dwi Aristi (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
Objective. This research aims to examine the influence of human resource competency, total quality management and the use of information technology on the business sustainability of hospitals in Pekanbaru. Research Method. This research uses quantitative research. The sample in this study was all hospital administration, finance and accounting employees in Pekanbaru. The data collection technique used was a questionnaire. The data analysis technique used is the multiple linear regression analysis method. The research results show that the human resource competency variable has a calculated t value of 2.401 and a significant level of 0.019. The total quality management variable has a calculated t value of 2.316 and a significant level of 0.023. The information technology utilization variable has a calculated t value of 2.214 and a significance level of 0.001. Conclusion. Human resource competency variables influence business sustainability. The total quality management variable influences business sustainability. The variable use of information technology influences business sustainability.